2016
DOI: 10.1039/c6sm00523c
|View full text |Cite
|
Sign up to set email alerts
|

Wetting against the nap – how asperity inclination determines unidirectional spreading

Abstract: We have carried out wetting experiments on textured surfaces with high aspect ratio asperities in the Wenzel state. When inclination is imparted to the asperities, we observe a strictly unidirectional spreading opposite to the direction in which the asperities point. The advancing contact angle decreases markedly as inclination increases. A crude numerical analysis successfully accounts for this behaviour, highlighting the interplay between Gibbs pinning at the top of the structures and imbibition along the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These results broaden the scope of the numerous studies made on the effect of periodic anisotropic surface pattern [2,3,4,5]. Indeed, most of investigations were made on sessile drops, which differs from the study of a dense pack of droplets (breath figure) [15,16,17,18,46,47,48].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…These results broaden the scope of the numerous studies made on the effect of periodic anisotropic surface pattern [2,3,4,5]. Indeed, most of investigations were made on sessile drops, which differs from the study of a dense pack of droplets (breath figure) [15,16,17,18,46,47,48].…”
Section: Resultsmentioning
confidence: 84%
“…The development of surface texturing techniques over the last 20 years has significantly advanced our understanding of surface wetting properties. Numerous studies have shown that the direction of a given surface pattern influences the orientation of sessile droplets by forming anisotropic droplets, oriented droplets or even self-propelled droplets [1,2,3,4,5,6,7,8]. Oriented structures favor droplet deformation and in effect, create anisotropic wetting as opposed to isotropic wetting [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus topographies inspired in hierarchical natural structures [5,6] and lithographic surfaces consisting of patterned lines [7,8] are commonly utilized to induce high water repellency [9] and low flow resistance [10][11][12]. Patterning using nanoparticles, [13] laser [14,15], etching [16,17] or plasma treatments [18] have been also used to tailor droplet sliding on surfaces. Similarly, a pin-release droplet effect has been reported on nanostructured thin films grown by physical vapor deposition at glancing angles (GLAD) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unidirectional liquid spreading is an extreme anisotropic wetting phenomenon, which means the liquid only spreads in one unique direction on the surface, but pins in all others. Anisotropic wetting properties can be achieved either by chemical modification [9][10][11][12][13][14] or surface topography [15][16][17][18][19][20]. Chemically modifying of surface is relatively simple and can achieve excellent anisotropic wetting properties, but lack of long-term stability.…”
mentioning
confidence: 99%
“…Chemically modifying of surface is relatively simple and can achieve excellent anisotropic wetting properties, but lack of long-term stability. In recent years, some literatures have successfully achieved unidirectional spreading property solely based on the microstructure of bent micro or nanopillars [15][16][17][18][19][20]. The wetting anisotropy of this type of structure relies on the asymmetry of the microstructure, as well as the contact angle (CA), which should be larger than a critical value (∼30°), such that the liquid does not spread reversely.…”
mentioning
confidence: 99%